BACTERIAL SPECTRUM AND ANTIMICROBIAL PATTERN OF BLOOD STREAM INFECTIONS ASSOCIATED WITH NON-TUNNELED DOUBLE LUMEN CATHETER IN HEMODIALYSIS PATIENTS - Hussain, Mehmood; Khan, Malik Nadeem Azam; Rehman, Khalid; Mirza, Irfan Ali; Rehman, Maryam; Riaz, Sidra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess Bacterial spectrum and antimicrobial pattern of Blood Stream Infections associated with non-tunneled double lumen catheter in hemodialysis patients.Study Design: Prospective observational study.Place and Duration of Study: Department of Nephrology, Pakistan Emirates Military Hospital Rawalpindi Pakistan; Armed Forces Institute of Pathology Rawalpindi, Pakistan, from May 2019 to Apr 2020.Methodology: A total of 753 patients underwent placement of non-tunneled double lumen catheter (457 femoral, 296 Internal Jugular). Patients with clinically suspected bloodstream infections had their catheters removed with tips being sent for culture along with 2 sets of peripheral blood cultures. Patients were labelled as having bloodstream infection if growth of organism was detected in catheter tip and at least one peripheral blood culture. Susceptibility testing was done for available antimicrobials.Results: One hundred and thirty six (18.06%) incidences or 5.48 bloodstream infections per 1000 catheter days, with confirmed growth on blood cultures were identified. Gram positive infections were seen in 76 (55.88%) individuals with most common organism being coagulase-negative Staphylococcus (28.68%), followed by Staphylococcus aureus (21.32%). These organisms had low resistance rates to Vancomycin (0%), Tigecycline (0%), Doxycycline (6.6%) and Linezolid (9.5%). Gram negative infections were seen in 60 (44.11%) patients with Klebsiella pneumoniae (13.24%) being the most commonly identified pathogen followed by Acinetobacter baumannii (12.50%) and had relatively higher degree of antimicrobial resistance.Conclusion: Gram positive organisms were the most common cause of bloodstream infection in this study and were found susceptible to vancomycin and doxycycline whereas gram-negative organisms had high rates of antimicrobial......